Characterization of the SWI/SNF complex and nucleosome organization in sorghum - Chen, Xiaofei; He, Chao; Xu, Huan; Zeng, Gongjian; Huang, Quanjun; Deng, Zhuying; Qin, Xiner; Shen, Xiangling; Hu, Yongfeng (Frontiers in Plant Science, 2024)
The SWI/SNF multisubunit complex plays an important role in the regulation of gene expression by remodeling chromatin structure. Three SWI/SNF complexes have been identified in Arabidopsis including BAS, SAS and MAS. Many subunits of these complexes are involved in controlling plant development and stress response. However, function of these complexes has hardly been studied in other plant species. In this study, we identified the subunits of the SWI/SNF complex in sorghum and analyzed their evolutionary relationships in 6 grass species. The grass species conserved all the subunits as in Arabidopsis, but gene duplication occurred diversely in different species. Expression pattern analysis in sorghum (Sorghum bicolor) showed that most of subunit-encoding genes were expressed constitutively, although the expression level was different. Transactivation assays revealed that SbAN3, SbGIF3, SbSWI3B possessed transactivation activity, which suggests that they may interact with Pre-initiation complex (PIC) to activate transcription. We chose 12 subunits in sorghum to investigate their interaction relationship by yeast two-hybrid assay. We found that these subunits displayed distinct interaction pattern compared to their homologs in Arabidopsis and rice. This suggests that different SWI/SNF complexes may be formed in sorghum to perform chromatin remodeling function. Through the integrated analysis of MNase-seq and RNA-seq data, we uncovered a positive relationship between gene expression levels and nucleosome phasing. Furthermore, we found differential global nucleosome enrichments between leaf and root, as well as in response to PEG treatment, suggesting that dynamics of nucleosome occupancy, which probably mediated by the SWI/SNF complex, may play important roles in sorghum development and stress response.